Essays in economic analysis and policy - Gehrels, Franz; Oliver, Henry Madison; Wilson, George Wilton (Bloomington ; London : Indiana University Press, 1970)
This book is divided into four parts: Part 1. Economics of Collective Action. Part 2. Recent Development in Monetary Theory. Part 3. Problems in the Analyses of Underdevelopment. Part 4. Karl Marx Revisited and the Workings of Centrally Administered Economies.
Includes bibliographical references.
rpm 20/02/2018
Loans
Keywords: Economics; Economic policy